Why one e‐business adoption model won't fit all firm sizes: The case of Lebanon's e‐service industry. Issue 5 (17th April 2020) - El Rassi, Mary Ann B.
Abstract: This study aims to determine the influential factors for e‐readiness among enterprises in developing countries based on their size. Given the well‐recognized value of e‐readiness in promoting e‐business in developing economies, and based on the Perceived e‐Readiness Model that was previously suggested in the literature, the study considered the impact of internal and external factors by firm size on the adoption of e‐business. Survey data were collected from 276 Lebanese senior managers operating in the e‐service industry, and a multiple discriminant function analysis was used to determine whether a set of variables is effective in predicting the e‐readiness of enterprises in two size categories, that is, large and small to medium enterprises. The study observed that the factors that influence enterprises' e‐business adoption vary depending on the firm's size and that one adoption model does not fit "e‐service firms" of different sizes. Large enterprises are more influenced by managers' commitment and the e‐readiness of supporting industries than their smaller counterparts. The research findings will be of interest to managers, policymakers, and academics in the e‐services industry.